Analisis Faktor-Faktor yang Mempengaruhi Praktik Akuntansi Manajemen pada Usaha Kecil dan Menengah di Kota Padang - Nurfaadhilah Nurfaadhilah; Dian Fitria Handayani (Jurnal Eksplorasi Akuntansi, 2023)
Small and medium enterprises (SMEs) create a major contribution to the country's economic growth. The development of SMEs can be encouraged by the use of management accounting practices (MAPs) as a basis for decision making in order that their business performances become effective and efficient in achieving goals. However, a few research has been done on MAPs in SMEs in developing countries. This study aims to show what contingency factors (company size, owner participation, market competition, and information technology) affect the implementation of MAPs in the SMEs sector in one of the SMEs central cities in developing country (Indonesia). namely the city of Padang. This study employs a quantitative descriptive survey method, by distributing questionnaires. A sample of 96 respondents was determined by purposive sampling technique. The respondents of the study are owners or staff/managers of SMEs accounting/finance. Multiple regression analysis with SPSS 29 is used to analyze the data. The results of the study conclude that the level of company size, owner participation, market competition, and information technology has a positive and significant effect on the implementation of MAPs by SMEs. This research is expected to be a reference for further research in the field of management accounting and corporate governance in SMEs.